Implementation Of The Use Of The C Programming Language in The Ubuntu Linux Operating System - Agus, Samsuriah (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The rapid pace of technological advancement has predominantly restricted the use of the C programming language to specific fields. This study aims to enhance accessibility to the C programming language for students and the general public on the Ubuntu Linux operating system. The research methodology employed is observational, facilitating the attainment of desired outcomes through systematic observation. This research focuses on implementing the C programming language within the Ubuntu Linux environment to validate its performance compared to its usage on Windows operating systems. The compilation and execution processes differ significantly on Ubuntu Linux, necessitating a distinct approach. Beyond validating these outcomes, the study aims to enhance user proficiency and understanding of C programming within the Ubuntu Linux environment. The Ubuntu Linux platform is essential for various scientific disciplines. The integration of the C programming language into the Ubuntu Linux operating system yields distinctive output displays, critical for advancing both information systems and broader fields of knowledge in alignment with evolving programming practices.